Cre-loxP-based system for removal and reuse of selection markers in Ashbya gossypii targeted engineering - Aguiar, Tatiana Quinta (2014)
The filamentous ascomycete Ashbya gossypii is amenable to genetic manipulation and is an excellent model system for studying eukaryotic cell biology. However, the number of selection markers in current use for both targeted gene integration and disruption in this fungus are very limited. Therefore, the Cre-loxP recombination system was adapted for use in A. gossypii and its effectiveness in recycling marker genes was demonstrated by constructing both single and double deleted Agura3 and Agade1 auxotrophic strains free of exogenous markers. In spite of its wide use, this is the first report in which the Cre-loxP system was applied to A. gossypii, opening new perspectives for targeted engineering of this fungus with several promising biotechnological applications.